Travels in the Colonies in 1773-1775 Described in the Letters of William Mylne - Calder, Jenni (Georgia Open History Library, 1993)
Travels in the Colonies in 1773-1775 Described in the Letters of William Mylne contains a narrative of the two years that Scottish architect and engineer William Mylne spent in the American colonies. The letters included in this volume, written from Mylne's own pen to his sister Anne and brother Robert, document Mylne's journeys from his home in Edinburg to the American colonies in South Carolina, Georgia, Charlestown, and New York. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.